Destination Image and Tourism Products to Visit Intention Tourism Object in Solok Regency: Mediation Role of Electronic Word of Mouth - Yulihardi, Yulihardi; Syaiful, Syaiful (Adpebi International Journal of Multidisciplinary Sciences, 2023)
This study aims to determine the effect of destination variables and tourism product variables on visiting intentions through (e-wom) at the Bukik Cinangkiak tourist attraction, Solok Regency. The research concept is a path analysis model used to the direct or indirect effect of a set of independent variables (exogenous) on the dependent variable (endogenous). The results of the analysis of the effect of the destination image on the intention to visit t count 2.562 > t table 1.661. The magnitude of the effect of 0.065 or 6.5% means that HO is accepted. Tourism product on intention to visit t count 4,297 > t table 1,661. The magnitude of the influence of 0.164 or 16.4% means that HO is accepted. Electronic word of mouth on intention to visit t count 4.410 > t table 1.661. The magnitude of the influence of 0.171 or 17.1% means that HO is accepted. Destination image to electronic word of mouth, t count 4,074 > t table 1.661. The magnitude of the influence of 0.149 or 14.9% means that HO is accepted. Tourism products on electronic word of mouth, t count 7,460 > t table 1,661. The magnitude of the effect of 0.372 or 37.2% means that HO is accepted. The indirect effect of destination image on intention to visit through electronic word of mouth is 0.519 or 51.9%. The indirect effect of tourism products on visiting intentions through electronic word of mouth is 0.581 or 58.1%.